Total endoscopic thyroidectomy after open neck biopsy of the follicular lymphoma of the thyroid gland. Issue 2 (12th August 2020) - Nakao, Atsushi; Saito, Yoshiyuki; Ikeda, Yoshifumi; Takami, Hiroshi; Hoshino, Go; Miyata, Ryohei; Tomita, Masato; Sato, Michio; Ishikura, Naoyo; Mitsuya, Toshiyuki; Ando, Nobutoshi
Abstract: Remote‐access total endoscopic thyroidectomy (TET) is a recently established approach that can avoid producing scars in the neck. There are no clear surgical indications for TET for benign nodules or for malignant tumors at present. We report a successful TET in a 50‐year‐old Japanese woman with follicular lymphoma of the thyroid gland after an open neck biopsy. She had been referred to us with a neck tumor noted 2 months earlier. Because of adhesion, we performed a combined resection of the thyroid and partial right sternohyoid muscle. To the best of our knowledge, there is no other report of a TET performed after open neck surgery. Our patient's case demonstrates that (a) the cosmetic outcome of TET is clearly superior to that of conventional open neck surgery, and (b) a TET can be suitable even for reoperation if carefully selected.